1992
DOI: 10.1159/000147305
|View full text |Cite
|
Sign up to set email alerts
|

Stereological Studies of the Parathyroid Gland of Phosphate-Treated Golden Hamsters Subjected to a Hypergravity Environment

Abstract: The ultrastructure of the parathyroid glands of phosphate-treated golden hamsters exposed to a 5-G environment was studied. In the phosphate-treated animals exposed to a hypergravity environment, the Golgi complexes associated with numerous prosecretory granules, and the enlarged intercellular spaces containing floccular or finely particulate material showed a significant increase compared to those of the control, centrifuged, and phosphate-treated groups, and the cisternae of the granular endoplasmic reticulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The present study demonstrated that in the Mg group the serum calcium level also showed a significant decrease in comparison with the control group. Furthermore, in the parathyroid glands of the 5G group the Golgi complexes and cisternae of the granular endoplasmic reticulum appeared to be increased and lipid droplets were significantly increased as compared to those of the control group, as observed in the parathyroid glands indicating increased functional activity in golden hamsters exposed exposed to a hypergravity environment (Shoumura et al, 1988a(Shoumura et al, , 1989a(Shoumura et al, , 1989bIsono et al , 1990;Shoumura et al , 1990Shoumura et al , , 1991aShoumura et al , , 1991bShoumura et al , , 1992aShoumura et al , , 1992bShoumura et al , , 1992c.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The present study demonstrated that in the Mg group the serum calcium level also showed a significant decrease in comparison with the control group. Furthermore, in the parathyroid glands of the 5G group the Golgi complexes and cisternae of the granular endoplasmic reticulum appeared to be increased and lipid droplets were significantly increased as compared to those of the control group, as observed in the parathyroid glands indicating increased functional activity in golden hamsters exposed exposed to a hypergravity environment (Shoumura et al, 1988a(Shoumura et al, , 1989a(Shoumura et al, , 1989bIsono et al , 1990;Shoumura et al , 1990Shoumura et al , , 1991aShoumura et al , , 1991bShoumura et al , , 1992aShoumura et al , , 1992bShoumura et al , , 1992c.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, ultrastructural reports have dealt with the problem on the influence of a hypergravity environment on the parathyroid gland (Sannes and Hayes, 1975; Shoumura et at., 1988a, 1989a, 1989b; Isono et al, 1990; Shoumura et al, 1990Shoumura et al, , 1991aShoumura et al, , 1991bShoumura et al, , 1992aShoumura et al, , 1992bShoumura et al, , 1992c.…”
Section: Discussionmentioning
confidence: 99%